2019
DOI: 10.18353/crustacea.49.0_1
|View full text |Cite
|
Sign up to set email alerts
|

The fish louse <i>Argulus coregoni</i> from <i>Oncorhynchus masou ishikawae</i> (Salmonidae) cultured in Shikoku, western Japan, with a list of occurrence records of <i>A. coregoni</i> from fishes reared in Japan

Abstract: Argulus coregoni Thorell, 1864 is briefly described based on specimens from the body surface of amago salmon, Oncorhynchus masou ishikawae Jordan & McGregor, 1925, cultured at a trout farm in Tokushima Prefecture, Shikoku, western Japan. This represents the first confirmed record of A. coregoni from farmed salmonids in Shikoku. A list of occurrence records of A. coregoni from fishes reared in Japan is also provided based on the literature published between 1950 and 2019. The species has so far been reported f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…The argulid branchiuran Argulus coregoni Thorell, 1864 is a skin parasite of freshwater fishes in northern Europe and eastern Asia (Neethling and Avenant-Oldewage 2016). In Japan, the species infects wild fishes belonging to five families; Salmonidae, Plecoglossidae (both Salmoniformes), Cyprinidae (Cypriniformes), Amblycipitidae (Siluriformes), and Odontobutidae (Gobiiformes) (e.g., Tokioka 1936;Yama guti 1937;Nagasawa and Kawai 2008;Nagasawa 2009Nagasawa , 2011Nagasawa et al 2014;Nagasawa and Ishikawa 2015;Nagasawa and Taniguchi 2021) but is also found on farmed salmonid and plecoglossid fishes (Hoshina 1950;Nagasawa and Yuasa 2020). Its larval development, host associations, impacts on host fishes, and treatment have all been studied (Inoue et al 1980;Shimura and Egusa 1980;Shimura 1981Shimura , 1983Shimura et al 1983a, b;Shimura and Inoue 1984;Kata hira et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The argulid branchiuran Argulus coregoni Thorell, 1864 is a skin parasite of freshwater fishes in northern Europe and eastern Asia (Neethling and Avenant-Oldewage 2016). In Japan, the species infects wild fishes belonging to five families; Salmonidae, Plecoglossidae (both Salmoniformes), Cyprinidae (Cypriniformes), Amblycipitidae (Siluriformes), and Odontobutidae (Gobiiformes) (e.g., Tokioka 1936;Yama guti 1937;Nagasawa and Kawai 2008;Nagasawa 2009Nagasawa , 2011Nagasawa et al 2014;Nagasawa and Ishikawa 2015;Nagasawa and Taniguchi 2021) but is also found on farmed salmonid and plecoglossid fishes (Hoshina 1950;Nagasawa and Yuasa 2020). Its larval development, host associations, impacts on host fishes, and treatment have all been studied (Inoue et al 1980;Shimura and Egusa 1980;Shimura 1981Shimura , 1983Shimura et al 1983a, b;Shimura and Inoue 1984;Kata hira et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…coregoni Thorell, 1864. These branchiurans are important parasites of farmed fishes as well, and their biology has been extensively studied in Japan [e.g., Nakazawa (1914), Tokioka (1936a), Kimura (1970), and Ikuta and Makioka (1997) for A. japonicus; Hoshina (1950), Shimura (1981Shimura ( , 1983, Nagasawa and Yuasa (2020), and Katahira et al (2021) for A. coregoni].…”
Section: Introductionmentioning
confidence: 99%
“…Argulus japonicus is morphologically similar to Argulus coregoni Thorell, 1864, which also occurs in east/southeast Asia, including Japan (e.g., Tokioka, 1936;Yamaguti, 1937;Hoshina, 1950;Nagasawa & Yuasa, 2020;Nagasawa & Taniguchi, 2021), Russian Far East (e.g., Dogiel & Akhmerov, 1952Smirnova, 1971;Gusev, 1987;Ermolenko, 2004;Sokolov et al, 2012), China (e.g., Wang, 1958;Institute of Hydrobiology, Hubei Province, 1973;Kuang & Qian, 1991;Yang, 2009), and Malaysia (Everts & Avenant-Oldewage, 2009). Argulus japonicus is distinguished from A. coregoni by having an apically rounded abdomen (Fig.…”
mentioning
confidence: 99%